The relationship between schizotypal personality features and mind wandering among college students during COVID-19 pandemic: A moderator of depression - Zhao, Guojun; Li, Shuangchen; Zhang, Qi; Guo, Xiaoxiao; Xie, Fusen; Yan, Shuhong; Liu, Haijian; Chong, Yuan; Ding, Yuee; Li, Xu (Frontiers in Psychiatry, 2023)
Although the impact of the COVID-19 pandemic on people's mental health has been well documented in many studies, the schizotypal personality features in the general population have not received sufficient attention. Study 1 is a longitudinal study tracking changes in schizotypal personality features among college students during the COVID-19 pandemic. A total of 153 Chinese college students were assessed using the Schizotypal Personality Questionnaire. The results showed that the scores from later stages in the pandemic were significantly higher than those from the initial stages on each dimension of schizotypal personality; which means that the schizotypal personality features became more obvious during the COVID-19 pandemic. Study 2 explored the relationship between schizotypal personality features, attention problem, and depression. A total of 557 college students completed the Schizotypal Personality Questionnaire, the Beck Depression Inventory, and the Mind-Wandering Questionnaire during the COVID-19 pandemic. The results showed that there were positive correlation between schizotypal personality features, depression and attention problem. Furthermore, depression played a moderating role on the relationship between schizotypal personality features and attention problem. In conclusion, the schizotypal personality features of college students increase during COVID-19; and it has positive relationship with attention problem; and depression moderates the relationship. We discussed these findings and provided some suggestions about future research.